A Study of the Poetic Foundations of Three Prominent Contemporary Poets Mehdi Akhavan Sales, Ahmad Shamloo and Hamid Mossadegh with an Approach to European Literature - Daneshvar Nike, Farshad (2021)
Literary schools in the West are influenced by the social and political conditions prevailing in those societies; This means that each school in line with the political and social developments of its time has undergone structural and content changes and gives way to a school with a different perspective. In the second half of the sixteenth century, medieval civilization collapsed and underwent many social, political, and religious changes. The group of many high-ranking landowners and feudal lords who had been forced to pay large sums of money as a result of the successive defeats of France in the Hundred Years' War were gradually forced to sell their lands and properties with all legal rights. The tribal kings belonged to it. This caused the landowners to lose their influence and power, and the government to change from a form of sectarian monarchy to an absolute monarchy. The king, like the ancient Romans, was considered to have absolute authority in the administration of the affairs of the country, and the lords of all lands served the king. By order of the Shah, ministries, the army, the Court of Accounts and the judiciary were formed; The bourgeoisie, meanwhile, entered government positions because of the prosperity of the commercial and industrial market, the wealthy and influential. Other important events, such as new inventions, new naval discoveries, as well as wars known as the Italian Wars, all went hand in hand and completely changed the way of life and the situation of French society. With the advent of Luther and Calvin and fundamental religious reforms, popular belief in the teachings of the clergy waned, and since then Christianity has been limited to a set of rites and ceremonies held by Catholic priests. In addition, Christian theologians gradually found themselves without the need for direct reference to Christian scriptures and recklessly discussed religious issues. On the other hand, in literary works, the desire for great ideas disappeared and literature, which was based on spiritual favors, became frozen. Religious plays lost their religious and heavenly appeal and took on the color of hypocrisy and trade; In this way, almost all the systems and laws that ruled France for centuries were questioned at the beginning of this century, and fundamental changes took place in Europe at that time; But it was not long before the great scientific and maritime discoveries showed him the power of human thought and greatness, and showed him that human endeavors must expand without borders, and that in a world full of contradictions and contradictions, he is free to go his own way. Choose. From then on, people liked what they thought was beautiful and charming; Therefore, not only the manifestations of the world of sensations and the world of nature were in the center of attention, but also the literary works of ancient writers and poets, especially ancient Greece, were doubly valued by them. This gradually led to the formation of a new attitude.